Non-motor symptoms in multiple system atrophy: A comparative study with Parkinson's disease and progressive supranuclear palsy - Hu, Wen-Zheng; Cao, Ling-Xiao; Yin, Jin-Hui; Zhao, Xue-Song; Piao, Ying-Shan; Gu, Wei-Hong; Ma, Jing-Hong; Wan, Zhi-Rong; Huang, Yue (Frontiers in Neurology, 2023)
Background: Non-motor symptoms (NMS) are compulsory clinical features for clinical diagnosis of multiple system atrophy (MSA), some of which precede motor symptoms onset. To date, few studies have systematically investigated NMS in MSA and timing of presenting NMS as the disease progresses. Clinically, MSA is difficult to be differentiated from Parkinson's disease (PD) and progressive supranuclear palsy (PSP), the differences in NMS between MSA and PD / PSP remain unclear. This study aimed to compare the burden of NMS between MSA and PD / PSP, and to delineate the timing of NMS presentation relative to the onset of motor symptoms in MSA. Methods: Sixty-one MSA, 87 PD, and 30 PSP patients were enrolled in this study. NMS were systematically assessed in all patients using the NMS scale (NMSS), and the onset of NMS relative to the onset of motor symptoms in MSA was investigated. Results: MSA group had higher total NMSS scores (82.15±46.10) than PD (36.14±30.78) and PSP (50.30±55.05) groups (p<0.001 overall). The number distribution pattern of NMS was significantly different among three parkinsonian disorders (p<0.001 overall). 85.2% patients with MSA had more than 10 NMS, which was significantly higher than PD (28.7%) and PSP (33.3%). The frequency and scores of many NMSS subdomains and symptoms were higher in MSA than in PD and PSP (All p<0.05). Multivariate logistic regression analysis revealed that patients with fainting, lack motivation, swallowing, loss of sexual interest could be attributed to MSA rather than PD or PSP, while patients with loss of concentration, forgetfulness were characteristic features of PD or PSP rather than MSA. REM-sleep behavior disorder (RBD), constipation, problems having sex, loss of sexual interest preceded motor symptoms onset of MSA by 2.81±4.51, 1.54±6.32, 1.35±4.70, 0.45±3.61 years, respectively. Conclusions: The NMS spectrum in MSA is different from those in PD and PSP. MSA patients have a higher NMS burden than patients with PD or PSP. RBD, constipation, problems having sex, loss of sexual interest may become early diagnostic clinical markers of MSA.